Kuwait : Financial Sector Assessment Program-Detailed Assessments of Observance of Standards and Codes-International Organization of Securities Commission (IOSCO)-Objectives and Principles of Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2004)
The Detailed Assessments of the Observance of Standards and Codes on the IOSCO Objectives and Principles of Securities Regulation on Kuwait review preconditions for effective securities regulation. The securities market in Kuwait is the second largest in the Arab world in terms of value of trading and market capitalization. A set of well-articulated and clear regulations and procedures governing public offering of securities, including tender offers, should be prepared and enforced. Rules governing mergers and acquisitions are not in place and need to be well defined.